EFEKTIVITAS KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN KAMPAR - Abdul Jabbar; Khairul Amri (ADISAM PUBLISHER, 2024)
The effectiveness of the performance of Civil Servants (PNS) is the level to which a person or group carries out their main duties to achieve the desired targets, the ability of Civil Servants to comply with obligations and avoid prohibitions specified in statutory regulations, Minister of Law and Human Rights Regulations. . Researchers found many interesting cases where the phenomenon is that in reality there are still many employees who commit violations such as not being there during working hours, arriving late and committing other violations, this is very interesting to research. This research aims to find out how effective the performance of employees in the civil service and human resource development agency is. According to Mangkumanegara's (2009) theory, performance is a work result achieved by a person in carrying out the tasks assigned to him which is based on skills, experience and commitment to time which is measured by considering quantity, quality and timeliness. The results of this research indicate that the performance effectiveness of employees in the Civil Service and Human Resources Department is still not going well. Judging from the fact that employees are still found who are not in the office during working hours, there is a lack of awareness and responsibility for what they have to do as employees. There are factors that influence the effectiveness of the performance of employees in the Civil Service and Human Resources Department, namely the level of success of work that is not suitable due to inefficient working hours, limited human resources who are experts in the work being carried out